2011
DOI: 10.1007/s10103-011-0975-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of optical coherence tomography and histopathology images of normal and dysplastic oral mucosal tissues

Abstract: Selecting the most representative site for biopsy is crucial in establishing a definitive diagnosis of oral epithelial dysplasia. The current process involves clinical examination that can be subjective and prone to sampling errors. The aim of this study was therefore to investigate the use of optical coherence tomography (OCT) for differentiation of normal and dysplastic oral epithelial samples, with a view to developing an objective and reproducible approach for biopsy site selection. Biopsy samples from pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…We expect enhanced backscattering at high spatial frequencies in HSIL owing to the presence of more and enlarged nuclei in its superficial epithelium. In this respect, we seek to confirm the observation of depth-dependent epithelial backscattering as reported in 2012 by Adegun et al 33 using optical coherence tomography.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…We expect enhanced backscattering at high spatial frequencies in HSIL owing to the presence of more and enlarged nuclei in its superficial epithelium. In this respect, we seek to confirm the observation of depth-dependent epithelial backscattering as reported in 2012 by Adegun et al 33 using optical coherence tomography.…”
Section: Resultssupporting
confidence: 55%
“…7(b) confirms the reported malignancy-related variation in depth-dependent epithelial backscattering. 33,50 In consequence, we study the ratio of epithelial backscattering at f ¼ 3 mm…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ex vivo studies have reported the ability of OCT to define cancer boundaries [6], and measure changes in tissue features associated with oral cancer diagnosis such as the thicknesses of the keratin layer, epithelial layer, and lamina propria, as well as identify the continuity of the basement membrane [7][8][9]. Quantitative analysis of the OCT attenuation coefficient in the epithelial layer of formalinfixed biopsy specimens has been employed to discriminate normal from mild, moderate and severe dysplasia with some success [10]. Several groups have performed in vivo oral cavity imaging to quantify epithelial thickness at different sites around the oral cavity [11,12], and identify tissue layers and microstructures [13].…”
Section: Introductionmentioning
confidence: 99%
“…Feasibility of OCT as a diagnostic tool has been demonstrated in various pre-clinical animal [24,25] and human [14,[26][27][28][29][30] oral cavity studies. Computational methods for automated OCT image analysis and classification [31], quantitative assessment [28,32] have been developed to aid diagnosis of oral cavity lesions. Polarization-sensitive OCT (PS-OCT) is an augmented OCT providing information of both structure and birefringence [33,34].…”
Section: Introductionmentioning
confidence: 99%